Ecology and control of introduced plants - Myers, Judith H., 1941- (Ecology, biodiversity, and conservation., 2003)
This book focuses on introduced plant species: where they come from, their impacts on native vegetation and ecosystems and the potential for their control. Aimed at advanced students and land managers, it contains practical explanations, case studies and an introduction to basic techniques for evaluating the impacts of invasive plants.